Analisis Perbaikan Posisi Kerja di Industri Pencacah Sampah Plastik Dengan Metode Quick Exposure Check (QEC) - Reiny Ditta Myrtanti; Septiari, Renny (Fakultas Teknik Universitas Tulang Bawang, 2024)
The wrong body position of workers while working can cause the risk of work accidents and cause complaints of illness, which will have a direct impact on reducing the worker's work productivity. To anticipate this, companies can improve work processes and activities to reduce risks or musculoskeletal complaints experienced by workers. Through the Quick Exposure Check (QEC) method carried out on workers, especially in the production section, workers' complaints due to incorrect work posture in the musculoskeletal area (back, shoulders, neck, arms and wrists) will be known so that recommendations can be made regarding process improvements. work for production workers and can reduce the risk of work-related injuries from the results of this analysis. From the research results, it was found that the QEC value for workers carrying out grinding/chopping, washing and drying work processes and activities was 65.34%; 60.79% and 64.77%, so there is a need for continued research and changes to workers' work processes and activities. With these changes, workers will be able to do work comfortably and reduce the risk of injury or musculoskeletal complaints in workers when doing work. Keywords: Improvement of work processes, Musculoskeletal, Quick Exposure Check (QEC), Work position